2001
DOI: 10.1046/j.1439-0523.2001.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Fusarium head blight and deoxynivalenol accumulation in wheat

Abstract: Fusarium head blight (FHB), caused by Fusarium graminearum Schwabe (telomorph =Gibberella zeae (Schw.)), is an important wheat disease world‐wide. Production of deoxynivalenol (DON) by F. graminearum in infected wheat grain is detrimental to livestock and is also a safety concern in human foods. An international collection of 116 wheat lines was evaluated for FHB resistance and concentration of DON in grain. Plants were inoculated with mixed isolates of F. graminearum in the greenhouse by injecting conidia int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
146
1
10

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(165 citation statements)
references
References 12 publications
8
146
1
10
Order By: Relevance
“…On the contrary, the variety Apache expressed the highest resistance to the accumulation of DON and ZEA, but FHB symptoms were clearly developed. Bai et al (2001) reported that severe visual symptoms may not always be associated with high DON levels, especially in varieties possessing moderate Type II resistance. Table 3 presents the results of correlation analyses.…”
Section: Results and Discussion Disease Development Under Different Cmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the variety Apache expressed the highest resistance to the accumulation of DON and ZEA, but FHB symptoms were clearly developed. Bai et al (2001) reported that severe visual symptoms may not always be associated with high DON levels, especially in varieties possessing moderate Type II resistance. Table 3 presents the results of correlation analyses.…”
Section: Results and Discussion Disease Development Under Different Cmentioning
confidence: 99%
“…Resistance to the pathogen spread can be more stable, but it is not so tightly linked with the natural course of infection. Low FHB severity due to Type I and Type II resistance usually coincides with low DON because of fewer infected kernels (Bai et al 2001). Other types of resistance described by Mesterházy (1995) are resistance to kernel infection, to toxin (DON) accumulation and tolerance.…”
mentioning
confidence: 99%
“…Disease severity was calculated as the proportion of symptomatic spikelets (PSS) per inoculated spike at 21st day after inoculation and used for QTL analysis. To validate the STS marker, additional 14 cultivars were evaluated for disease severities by the same method (Bai et al, 2001). …”
Section: Plant Materials and Fhb Evaluationmentioning
confidence: 99%
“…On the other hand, Sultan and apparently also Federer (at a higher resistance level) can be classified according to these experiments as varieties producing less DON at a higher symptom expression and greater grain weight reduction. Bai et al (2001) reported that severe visual symptoms may not always be associated with high DON levels, especially in the varieties possessing a moderate Type II resistance.…”
Section: Evaluation Of the Variety Resistance To Accumulation Of Don mentioning
confidence: 99%
“…To minimize year/location effects on results, it appears often necessary to support disease development by irrigation of plots. Low FHB severity due to Type I and Type II resistance usually coincides with low DON because of fewer infected kernels (Bai et al 2001). Other types of resistance described by Mesterházy (1995) are resistance to kernel infection, to toxin (DON) accumulation and tolerance.…”
mentioning
confidence: 99%